Adequate utilisation of emergency services in Germany: a differential by migration background?. (13th November 2019) - Sauzet, O; David, M; Naghavi, B; Borde, T; Sehouli, J; Razum, O
Abstract: Background: The role of emergency services (ES) is to provide a round-the-clock acute care. In recent years, inadequate use of emergency services has been internationally thematised because of overcrowding and the cost associated. There is only limited evidence regarding the pattern of utilisation of ES by populations with a migration background. Methods: Consecutive patients visiting three ES in Berlin from July 2017 to July 2018, and who fulfilled inclusion criteria such as being conscious, were recruited into the study. A questionnaire covered medical conditions, reasons to visit the ES, and socio-economic factors. A criterion for the adequacy of utilisation was developed using a sub-sample of patients with information provided by physicians. Differences between migrants (1st generation), their offspring (2nd generation), and non-migrants were evaluated using logistic regression. Results: 2 327 patients were included, 901 had a migration background. The utilisation was adequate if the patient was admitted to hospital and/or if all three following criterion were fulfilled: reported to have been advised by a physician to visit the ES; reported strong pain; and reported a high perceived urgency (both ≥7 on a scale from 0 to 10). Adjusting for gender, age, condition and number of recent visits to ES, 1st generation migrants had a significantly higher chance than non-migrants to have an inadequate utilisation of services (OR 1.30; 95% CI [1.01; 1.68]). For 2nd generation persons, this was not statistically significant. Conclusions: First generation migrants have a higher chance of inadequate ES use compared to non-migrants. A similar study 20 years ago had similar findings. This implies that existing information leaflets on ES addressing specific population groups are not sufficient to improve adequacy of use. Structural changes in the healthcare system as well as improved methods of communication respecting the needs of diverse subgroups of patients need to be considered. Key messages: Existing information leaflets on emergency services addressing specific population groups are not sufficient to improve adequacy of use. Structural changes in the healthcare system as well as improved methods of communication respecting the needs of diverse subgroups of patients need to be considered.